QUALITY SERVICES ANALYSIS OF SPORT SERVICES INDUSTRY BY SERVQUAL AND IMPORTANCE PERFORMANCE ANALISYS (IPA) METHOD - Veron Farminta; Sigit Mujiharjo; Karona Cahya Susena (BPFP Faperta UNIB, 2015)
In the field of both services and manufacturing industry, the quality is very important, especially in terms of quality of service. If a good quality of service, the company will be ready to face market competition/business but if the quality of customer service is less satisfactory then be prepared to face setbacks. One method that can be used to evaluate the quality of service is a method servqual and imfortance performance analisys (IPA). Both methods are used to see how far the quality of performance / service provided when viewed from the expectations or interests of customers / consumers. Anonimus is where researchers conduct studies using both methods. The result showed that some of the dimensions that must be improved, namely: good field conditions (artificial turf, goal, balls, nets), organized the tournament, Anonimus Parties must be able to be responsive in dealing with problems that arise and Security Assurance Goods customers in the locker Room. Keywords :